Using Computer Generated Assignments to Enhance Learning - Suwardy, Themin (Institutional Knowledge at Singapore Management University, 2000)
The assignment generator is a unique way of offering intellectual stimulation to students by providing them with different assignment data sets based on the same assignment specification. Due to the nature of first year accounting subjects, it is important to give students a major assignment that encompasses the full accounting cycle from journalising transactions through to preparing financial statements. Unfortunately, if all students have the same assignment specifications, the assignment is highly duplicable and the process may be seen to encourage cheating. The assignment generator provides unique assignments for each student and thus is one way of addressing the potential for cheating.